Lao People's Democratic Republic - Investment and Access to Land and Natural Resources : Challenges in Promoting Sustainable Development, A Think Piece (A Basis for Dialogue) - Lao PDR Ministry of Planning and Investment; World Bank (World Bank, Washington, DC, 2013)
The aim of this discussion paper is to ascertain the government of Lao's (GoL) current practices in negotiating, awarding, and managing land concessions; enhance GoL understanding and commitments to develop national capacities targeting improved land management, that will generate revenues for GoL, and ensure sustainable development as an urgent priority; and provide a basis for dialogue within the government to enable its determination of priorities to better address land development issues in Laos, to enable the achievement of sustainable, responsible economic development. The paper also examines key issues revolving around the sustainable utilization of land, and the mechanisms, through an examination of GoL s policy statements. The findings are provided, and the report advises that GoL pay special attention to four major points: the availability of adequate and accurate information on which to make decisions on concessions; adequate capacity within GoL agencies to determine, award and monitor/oversee the operation of concessions; and governance over land and natural resources. These points of guidance are expected to contribute towards developing sustainable approaches for land administration and management programs in Lao PDR, and enabling GoL to adopt more rigorous oversight of the land and natural resources sector, as well to the political economy aspects of resource management.